KEANEKARAGAMAN INSEKTA (ORDO LEPIDOPTERA) DI PUSAT SUAKA SATWA ELANG JAWA BOGOR - Rizky Krismawanti; Teti Rostikawati; Dimas Prasaja (EKOLOGIA, 2021)
The Javan Eagle Wildlife Sanctuary Center (PSSEJ) is one of the regions in Indonesia that has a high diversity of flora and fauna in Bogor, West Java. One of the fauna that live in PSSEJ is an insect of the order Lepidoptera. The limited information about Lepidoptera in this location causes the data on the diversity of these species to not be known with certainty. It is necessary to research the diversity of Lepidoptera. This study aims to study the species diversity of the order Lepidoptera at the Javan Eagle Wildlife Sanctuary Center. This research is an exploratory research conducted from December 2020 to August 2021 in two routes, namely track 1 (camping ground area) and route 2 (officer entrance route and land use). The research method uses a survey method using a sweeping net technique. Collecting data in the form of primary data covering the number of Lepidoptera species and secondary data covering temperature, humidity and light intensity. Based on the research, it was found 39 species of the order Lepidoptera with a moderate diversity index of 2.84, a high evenness index of 0.87 and a low dominance index of 0.08. Keywords: Diversity, Javan Eagle Sanctuary Center, Lepidoptera